Postoperative admission to paediatric intensive care after tonsillectomy. (May 2020) - Levi, Eric; Alvo, Andrés; Anderson, Brian J; Mahadevan, Murali
Objectives: To review interventions required by children admitted for intensive care management following tonsillectomy or adenotonsillectomy either as elective or unplanned admission in a tertiary children's hospital. Methods: A retrospective chart review over a 10-year period between April 2007 and March 2017 was performed. Charts were interrogated for treatments that were administered in the paediatric intensive care unit. Respiratory support therapies such as supplemental oxygen administration, high-flow nasal oxygen, positive pressure ventilation, continuous positive airway pressure, airway interventions and tracheal intubation were reviewed. Results: There were 103 children admitted to the paediatric intensive care unit following tonsillectomy or adenotonsillectomy. The average age was 6.2 years (range 7 months–17 years). The main indications for the procedure were sleep disordered breathing or obstructive sleep apnoea syndrome. In all, 53 children had syndromes with medical comorbidities, 31 were current continuous positive airway pressure users and 5 had a tracheostomy in situ. Forty children admitted to paediatric intensive care unit did not require any high-level care. Ten children who had an unplanned admission had their respiratory interventions started in the theatre or in the post-anaesthetic care unit, before paediatric intensive care unit admission, and did not require escalation of care. Conclusion: Children may not require admission for intensive care after tonsillectomy if they have had an incident-free period in the post-anaesthetic care unit. Some of those who required high-flow nasal oxygen could have been managed on the ward provided with adequate training and monitoring facilities. The level of care they require in post-anaesthetic care unit reflected the level of care for the immediate postoperative period in the paediatric intensive care unit.